Do baseline characteristics and treatments account for geographical disparities in the outcomes of patients with newly diagnosed atrial fibrillation? The prospective GARFIELD-AF registry. Issue 1 (7th January 2022) - Fox, Keith A A; Virdone, Saverio; Bassand, Jean-Pierre; Camm, A John; Goto, Shinya; Goldhaber, Samuel Z; Haas, Sylvia; Kayani, Gloria; Koretsune, Yukihiro; Misselwitz, Frank; Oh, Seil; Piccini, Jonathan P; et al.
Abstract : Objective: In patients with newly diagnosed atrial fibrillation (AF), do baseline risk factors and stroke prevention strategies account for the geographically diverse outcomes. Design: Global Anticoagulant Registry in the FIELD-Atrial Fibrillation is a prospective multinational non-interventional registry of patients with newly diagnosed AF (n=52 018 patients). Setting: Investigator sites (n=1317) were representative of the care settings/locations in each of the 35 participating countries. Treatment decisions were all determined by the local responsible clinicians. Participants: The patients (18 years and over) with newly diagnosed AF had at least 1 investigator-determined stroke risk factor and patients were not required to meet specific thresholds of risk score for anticoagulant treatment. Main outcomes and measures: Observed 1-year event rates and risk-standardised rates were derived. Results: Rates of death, non-haemorrhagic stroke/systemic embolism and major bleeding varied more than three-to-four fold across countries even after adjustment for baseline factors and antithrombotic treatments. Rates of anticoagulation and antithrombotic treatment varied widely. Patients from countries with the highest rates of cardiovascular mortality and stroke were among the least likely to receive oral anticoagulants. Beyond anticoagulant treatment, variations in the treatment of comorbidities and lifestyle factors may have contributed to the variations in outcomes. Countries with the lowest healthcare Access and Quality indices (India, Ukraine, Argentina, Brazil) had the highest risk-standardised mortality. Conclusion: The variability in outcomes across countries for patients with newly diagnosed AF is not accounted for by baseline characteristics and antithrombotic treatments. Residual mortality rates were correlated with Healthcare Access and Quality indices. The findings suggest the management of patients with AF needs to not only address guideline indicated and sustained anticoagulation, but also the treatment of comorbidities and lifestyle factors. Trial registration number: NCT01090362 .